Long non-coding rnas as key modulators of the immune microenvironment in hepatocellular carcinoma: implications for Immunotherapy - Zhao, Siqi; Chen, Fei; Hu, Lingyu; Li, Xiaoping; Gao, Zhaofeng; Chen, Minjie; Wang, Xiaoguang; Song, Zhengwei (Frontiers in Immunology, 2025)
Hepatocellular carcinoma (HCC) represents a major global health challenge, characterized by its complex immune microenvironment that plays a pivotal role in tumor progression and therapeutic response. Long non-coding RNAs (lncRNAs) have emerged as critical regulators of various biological processes, including gene expression and immune cell function. This review explores the multifaceted roles of lncRNAs in modulating the immune microenvironment of HCC. We discuss how lncRNAs influence the infiltration and activation of immune cells, shape cytokine profiles, and regulate immune checkpoint molecules, thereby affecting the tumor’s immunogenicity and response to immunotherapy. Furthermore, we highlight specific lncRNAs implicated in immune evasion mechanisms and their potential as biomarkers and therapeutic targets. By elucidating the intricate interplay between lncRNAs and the immune landscape in HCC, this review aims to provide insights into novel strategies for enhancing immunotherapeutic efficacy and improving patient outcomes.